Improvement of IRI B0, B1 and D1 at mid-latitude using MARP - Blanch, E. (2006)
Comparative analysis of predicted parameters B0, B1 and D1 by IRI-2001model (International Reference Ionosphere) and those obtained from the Monthly Averaged Representative Profiles (MARP) at mid-latitude station shows significant disagreement. The linear coefficient of determination between the model-predicted and expected (MARP) values are about R 2 ∼ 0.45, 0.22, and 0.15 for B0, B1 and D1, respectively. A Local Model (LM) created using a general least-square fit to a harmonic function of these parameters obtained by MARP simulating the diurnal, semidiurnal and seasonal variations improves the linear coefficient of determination between the expected and IRI-predicted parameters by factor of two. The coefficients obtained from this model could be implemented into the IRI software to improve calculations of the parameters B0, B1 and D1.